VOWEL AND DIPHTHONG FOSSILIZATION OF ENGLISH TEACHERS’ SPEECH IN YOGYAKARTA HIGH SCHOOL CLASSROOM - Adevia Ananda; Surono; Fauzia (Indonesian EFL Journal, 2026)
This study aims to identify the forms of vowel and diphthong pronunciation fossilization that occurs in English as a Foreign Language Teachers (EFLTs) in a high school in Yogyakarta. As well as analyzing external and internal factors that contribute to the process. This study uses a qualitative methodology with a case study design. And involves two experienced English teachers who were purposively selected to be involved in this study. Data were collected through classroom observations, video recordings of learning, and in-depth interviews. Data analysis included the process of data reduction, data presentation, and drawing conclusions. The results of the study indicate that both EFLTs experienced pronunciation fossilization in vowels (/ə/, /ɪ/, /ʌ/, /uː/, /æ/, /ɜː/, /ɔː/, /iː/) and diphthongs (/eɪ/, /aɪ/, /əʊ/, /aʊ/, /eə/, /ɪə/). This fossilization is influenced by external factors such as a lack of systematic phonological feedback and limited exposure to authentic English in the school environment and internal factors such as L1 phonological interference, difficulty in distinguishing similar sounds, long-established articulatory habits, psychological attitudes that support pronunciation errors, and teaching experience without ongoing phonetic reflection. Therefore, this study suggests that ongoing phonetic training focused on vowel and diphthong contrasts can increase access to appropriate pronunciation models and foster a culture of phonological correction in the school environment.